Molecular modeling of lupeol for antiviral activity and cellular effects - P. B. Lalthanpuii, C. Lalrinmawia, B. Lalruatfela, Lal Ramliana, K. Lalchhandama (Journal of Applied Pharmaceutical Science, 2023)
Lupeol is a naturally occurring pentacyclic triterpenoid present in several plants and is attributed to have anticancer, antiparasitic, and anti-inflammatory properties. Owing to its known antipathogenic and immunomodulatory activities, an in silico study was done on its potential interactions with various surface proteins of SARS-CoV-2, a coronavirus that causes COVID-19. Molecular docking indicated that it binds effectively with SARS-CoV-2 proteins that are vital to the life cycle, structural integrity, and virulence of the virus. It showed high binding affinities on the main protease, nucleocapsid phosphoprotein, papain-like protease, RNA-dependent RNA polymerase, and spike glycoprotein. It was also analyzed for its possible targets on various proteins critical to immune signaling pathways, as well as for its cellular absorption, distribution, excretion, metabolism, and toxicity. The findings suggest that lupeol is a potential drug candidate as an antiviral medication against coronavirus and for immune-related disorders.
Keywords: Antiviral activity, lupeol, molecular docking, SARS-CoV-2, target proteins